Hepatic arterial therapy with oxaliplatin and systemic capecitabine for patients with liver metastases from breast cancer. (February 2019) - Lindgaard, S.C.; Brinch, C.M.; Jensen, B.K.; Nørgaard, H.H.; Hermann, K.L.; Theile, S.; Larsen, F.O.; Jensen, B.V.; Michelsen, H.; Nelausen, K.M.; Holm, V.H.; Ekblad, L.; et al.
Abstract: Objectives: Hepatic arterial treatment (HAT) for liver metastases in patients with metastatic breast cancer (MBC) has only been investigated in few studies. Materials and methods: Two phase II trials were initiated simultaneously to evaluate capecitabine in combination with oxaliplatin in patients with MBC and liver metastases. These two trials are reported together. Continuous capecitabine (1300 mg/m2) was combined with oxaliplatin (85 mg/m2) alternating between systemic treatment and HAT followed by degradable starch microspheres with EmboCept ® S every second week. Four patients participated in a pharmacokinetic analysis of oxaliplatin. Each patient had samples taken when receiving oxaliplatin systemically and as HAT with and without EmboCept ® S. Results: Totally, 52 patients received HAT: 14 with liver metastases only and 38 patients with additional limited metastatic disease. The patients had previously received a median of 2 (range 0–6) chemotherapeutic regimens for MBC. The response rate was 42.3% (95% confidence interval (CI) 28.7–56.8%) with 7.7% complete and 34.6% partial responses. Median progression free survival was 10.8 months (95% CI 6.9–14.7 months) and median overall survival 27.6 months (95% CI 20.4–34.8 months). The toxicity was moderate with hand-foot syndrome (15.4%), neuropathy (9.6%), fatigue (9.6%), and abdominal pain (9.6%) being the most common grade 3 adverse events. There was no clear difference between systemic blood concentrations of oxaliplatin when given systemic or as HAT. Conclusion: HAT oxaliplatin in combination with capecitabine is safe and efficient in patients with MBC. The results are promising with high response rates and a long median progression free and overall survival. Highlights: HAT with oxaliplatin in patients with MBC is safe and efficient. In these phase 2 trials, the overall RR was 42.3%, median PFS 10.8 months, and median OS 27.6 months. HAT represents a potential loco-regional treatment for liver metastases. Abdominal pain was only seen after intrahepatic treatment but was manageable. Besides abdominal pain, toxicity was comparable and manageable between i.v. and HAT administrations.